MAKNA SIMBOLIK DALAM UPACARA SORONG SERAH AJI KERAME PADA PERKAWINAN ADAT SASAK DI DESA PERINA - Suud; Isa Al-ansoriy; Syafruddin (Journal of Social Education Sasambo, 2025)
The purpose of this study was to determine the process of the sorong serah aji krame ceremony in Perina Village and to analyze the symbolic meaning of the properties contained in the process of the sorong serah aji krame ceremony in Perina Village. This study used a qualitative approach with an ethnographic study method. The research location is in Perina Village, Jonggat District, Central Lombok Regency. Primary data were obtained through non-participant observation and semi-structured interviews with research informants, while secondary data were obtained through books, articles, scientific journals, government institution profiles, and statistical data. Data analysis in this study was carried out through the stages of data reduction, data presentation, verification, and drawing conclusions. The results showed that in the sorong serah process there are three stages, namely: 1) preparation of the belongings, 2) preparing the penyorong, and 3) implementation of the sorong serah process or customary session. Furthermore, the symbolic meaning of the traditional properties used was found, including napak lemah, olen-olen, salin dede, pelengkak, otak beli, and pemegat. Suggestions based on the results of this study are: 1) for the village government, especially the village head, to better demonstrate and maintain the sustainability of existing traditional culture, and 2) the people of Perina Village are expected to continue to preserve the existing culture and develop it in their daily lives.